ANALISA PERBANDINGAN EFEKTIVITAS SISTEM PENJUALAN SECARA DIGITAL DAN NON DIGITAL PRODUK MIE KERING PT. SURYA PRATISTA HUTAMA - Rizky Marshanda Putri Arifin; Miya Dewi Suprihandari (PUTRA JAWA PUBLISHER, 2024)
PT Surya Pratista Hutama (SUPRAMA) is one of the major industries producing dry noodles in East Java. To expand and develop its dry noodle products, a well-structured and evenly distributed sales system is crucial for sustained business growth. In this context, both digital and non-digital sales systems have emerged as viable options. Particularly in this digital age, numerous tools and platforms facilitate business development for entrepreneurs. The research methodology employed in this study is qualitative, utilizing an evidence-based literature review approach. Every business requires an efficient and appropriate sales system to support continuous growth. Consequently, companies must adopt both digital and non-digital sales strategies. Digital sales systems, prevalent in today's technological landscape, offer ease and speed in conducting transactions. Findings from this study underscore the significant impact of digital and non-digital sales systems on business development, representing a progressive step towards enhancing business awareness. Expanding distribution networks and intensifying promotional efforts through digital marketing are key strategies highlighted in this research.